Identification of Candidate Auxin Response Factors Involved in Pomegranate Seed Coat Development - Yu, Li’ang; Liu, Chunyan; Li, Jiyu; Jia, Botao; Qi, Xiaoxiao; Ming, Ray; Qin, Gaihua (Frontiers in Plant Science, 2020)
Auxin response factors (ARFs) are transcription factors, regulating the auxin signaling pathways involved in plant development and related processes. In this study, we performed the genome-wide identification and characterization of ARFs in pomegranate and compared them with ARFs from three other species. Seventeen PgrARFs were identified and clustered into four groups, according to their phylogenetic relationship with the remaining 59 ARFs. A recent whole-genome duplication event in pomegranate may have contributed to the expansion and diversification of PgrARFs. Genomic truncation and variant splicing mechanisms contributed to the divergence of PgrARFs, a conclusion that was supported by different exon-intron structures of genes and incomplete conserved domains of PgrARFs in a specific phylogenetic group (group III). Interestingly, the absence of motifs from certain PgrARF genes corresponded to their low transcription levels, which contrasted to the highly expressed PgrARFs with intact motifs. Specifically, PgrARF1 and PgrARF2 highly expressed in both inner and outer seed coat, and phylogenetically related to Arabidopsis orthologs which mediates cell divisions in seed coat. We infer these two PgrARFs might involve in seed coat development through cell divisions in response to auxin regulation. These findings provided information on the characteristics and evolutionary relationships of PgrARFs, but also shed lights on their potential roles during seed coat development in pomegranate.